Pex14p Phosphorylation Modulates Import of Citrate Synthase 2 Into Peroxisomes in Saccharomyces cerevisiae - Schummer, Andreas; Maier, Renate; Gabay-Maskit, Shiran; Hansen, Tobias; Mühlhäuser, Wignand W. D.; Suppanz, Ida; Fadel, Amir; Schuldiner, Maya; Girzalsky, Wolfgang; Oeljeklaus, Silke; Zalckvar, Einat; Erdmann, Ralf; et al. (Frontiers in Cell and Developmental Biology, 2020)
The peroxisomal biogenesis factor Pex14p is an essential component of the peroxisomal matrix protein import machinery. Together with Pex13p and Pex17p, it is part of the membrane-associated peroxisomal docking complex in yeast, facilitating the binding of cargo-loaded receptor proteins for translocation of cargo proteins into the peroxisome. Furthermore, Pex14p is part of peroxisomal import pores. The central role of Pex14p in peroxisomal matrix protein import processes renders it an obvious target for regulatory mechanisms such as protein phosphorylation. To explore this possibility, we examined the state of Pex14p phosphorylation in Saccharomyces cerevisiae. Phos-tag-SDS-PAGE of Pex14p affinity-purified from solubilized membranes revealed Pex14p as multi-phosphorylated protein. Using mass spectrometry, we identified 16 phosphorylation sites, with phosphorylation hot spots located in the N- and C-terminal regions of Pex14p. Analysis of phosphomimicking and nonphosphorylatable variants of Pex14p revealed a decreased import of GFP carrying a peroxisomal targeting signal type 1, indicating a functional relevance of Pex14p phosphorylation in peroxisomal matrix protein import. We show that this effect can be ascribed to the phosphomimicking mutation at serine 266 of Pex14p (Pex14p-S266D). We further screened the subcellular distribution of 23 native GFP-tagged peroxisomal matrix proteins by high-content fluorescence microscopy. Only Cit2p, the peroxisomal isoform of citrate synthase, was affected in the Pex14p-S266D mutant, showing increased cytosolic localization. Cit2p is part of the glyoxylate cycle, which is required for the production of essential carbohydrates when yeast is grown on nonfermentable carbon sources such as oleic acid. Reactions of the glyoxylate cycle are partitioned between peroxisomes and the cytosol. Our data point to the control of the peroxisomal import of Cit2p via the state of Pex14p phosphorylation at S266, which may help S. cerevisiae cells to rapidly adjust their carbohydrate metabolism according to the nutritional conditions.